Inflammation: A Novel Therapeutic Target/Direction in Atherosclerosis - Li, Bin; Li, Weihong; Li, Xiaoli; Zhou, Hong (Current Pharmaceutical Design, 2017)
Over the past two decades, the viewpoint of atherosclerosis has been replaced gradually by a lipiddriven, chronic, low-grade inflammatory disease of the arterial wall. Current treatment of atherosclerosis is focused on limiting its risk factors, such as hyperlipidemia or hypertension. However, treatment targeting the inflammatory nature of atherosclerosis is still very limited and deserves further attention to fight atherosclerosis successfully. Here, we review the current development of inflammation and atherosclerosis to discuss novel insights and potential targets in atherosclerosis, and to address drug discovery based on anti-inflammatory strategy in atherosclerotic disease.
Keywords: target identification